Scaling up and kinetic model validation of Direct Black 22 degradation by immobilized Penicillium chrysogenum - Durruty, Ignacio (2018)
This research was undertaken to develop tools that facilitate the industrial application of an immobilized loofah-fungi system to degrade Direct Black 22 (DB22) azo dye. In laboratory-scale tests, the DB22, and loofah as support, were used. Assays without loofah were used as a free-cells control. The use of natural carriers to facilitate adhesion and growth of the fungi has shown favorable results. The degradation rate of immobilized cells increased twice as compared to free-cells control. At day 5 the decolorization was almost complete, while without loofah the total decolorization took more than 10 days. After 10 days, the extent of growth was nine times higher for the immobilized assays in comparison with the control flask. In subsequent experiments decolorization of DB22 was proven in a bench-scale reactor. A previously developed kinetic model was validated during the process. The model validation over free-cells assays gives an average normalized root mean squared error (ANRMSE) of 0.1659. Recalibration steps allowed prediction of the degradation with immobilized cells, resulting in an ANRMSE of 0.1891. A new calibration of the model during the scaling-up process yielded an ANRMSE of 0.1136 for DB22. The results presented encourage the use of this modeling tool in industrial scale facilities.